Pengaruh kualitas pelayanan terhadap kepuasan pelanggan jasa service sepeda motor honda pada ahass cv. padat karya samarinda - Imam Fauzi; Suharno Suharno; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aimed to determine the effect of the quality of services tangible, reliability, assurance, responsiveness and empathy for customer satisfaction, and the variable quality of Which the dominant service to customer satisfaction AHASS CV. Padat Karya Samarinda. Sampling in this study used a non-probability sampling method, using incidental sampling technique. The samples are customer AHASS CV. Padat Karya Samarinda. The samples used were 98 respondents. Data analysis method used is Multiple Linear Regression using SPSS version 23. The results of this study indicate that the variable quality of service that consists of tangible, reliability, assurance, responsiveness and empathy simultaneously significant positive effect on customer satisfaction. In partial assurance significant positive effect on customer satisfaction, while variable tangible, reliability, responsiveness and empathy had no significant positive effect, so that the variable quality of service the dominant influence on customer satisfaction AHASS CV. Padat Karya Samarinda is a assurance.